The Effect of Solvent Use on Biodiesel Production from Spent Bleaching Earth (SBE) via Staged In Situ Transesterification - Miftahurrahmah; Melysa Putri; Netri Elisma (Eksergi, 2026)
This study investigates the effect of solvent and co-solvent systems on biodiesel production from spent bleaching earth (SBE) via staged in situ transesterification. The proposed approach integrates solvent-assisted extraction and transesterification in a staged sequence to enhance oil recovery and fatty acid methyl ester formation from a solid waste feedstock. Methanol–hexane and ethanol–hexane systems were evaluated at various SBE-to-co-solvent ratios and transesterification times. The results indicate that methanol-based systems consistently produced higher biodiesel yields than ethanol-based systems, with optimal performance observed at an SBE-to-co-solvent ratio of 1:3 and a transesterification time of 90 minutes. GC–MS analysis provided chemical evidence of ester formation, revealing the presence of palm oil–derived fatty acid methyl esters, with the highest total methyl ester content (44.74%, area %) obtained under methanol-based conditions at a ratio of 1:3. Overall, the findings highlight the critical role of solvent selection and staged processing in improving biodiesel recovery and ester formation from spent bleaching earth.